Prevalence of Common Functional Gastrointestinal Symptoms in Infants in Srinagarind Hospital - Dolchalermyuttana, Parichart; Kosuwon, Pensri (Srinagarind Medical Journal, 2015)
Background and Objectives: Functional gastrointestinal disorders are common in infants. The clinical symptoms including infant regurgitation, infant colic, infant dyschezia and functional constipation lead to recognition of their parents. These symptoms leads parents bring infants to see doctors for medications or change milk formula, but naturally these symptom can decline by themselves in proper time. This aim to determine the prevalence of gastrointestinal symptoms suggestive of an infant/toddler functional gastrointestinal disorder (FGID) by Romes III criterias as reported by parents from questionnaires and managements of parents for their child’s symptoms. Method : Study design cross sectional study. Populations parents (n= 339) of children aged 0-2 years old were recruited in well baby clinics at Srinagarind hospital and completed a questionnaire about their child’s gastrointestinal symptoms. Results : 39.5% of infants/toddlers qualified for FGIDs and meet for Rome III criteria for 27%, the most prevalent were the infant regurgitation at 20%, infant dyschezia at 15%, infant colic at 8.9%, and functional constipation at 5.6% respectively. Observation of parents was the most common management in all FGIDS. Conclusions : FGIDs are common and can be identified in the general population, Infant regurgitation was the most common FGID in infants. Observation of parents was the most management in all symptoms.